Studi Struktur Mikro dan Jenis Mineral Batuan Tanah Beruap di Gunung Soputan Minahasa - Jonathan J. Wuisan; Donny R. Wenas; Alfrie M. Rampengan; Cyrke A. N. Bujung (Jurnal FisTa : Fisika dan Terapannya, 2022)
Geothermal is one of the natural resources that has great potential to be used as a renewable energy. The existence of geothermal sources is characterized by the presence of geothermal manifestations that appear on the earth's surface. North Sulawesi Province is one of the areas that have alteration rocks that are commonly found in geothermal manifestation areas. The purpose of this study was to determine the elemental composition and types of minerals in steaming ground at Mount Soputan in Minahasa, North Sulawesi Province. The method used is the electron beam method on SEM, and the energy dispersive X-ray spectroscopic method and FTIR spectroscopy. The results obtained indicate that the elemental composition of the steaming ground in Mount Soputan in Minahasa, North Sulawesi Province is Al, Si, and Fe with the percentage content of Al 8.53 percent, Si 87.13 percent, and Fe 4.34 percent. Types of rock minerals on the steaming ground at Mount Soputan, Minahasa Regency obtained quartz and magnetite minerals, which are dominated by quartz.